A three-dimensional planned osteotomy on the zygomatic arch for reduction malarplasty. Issue 8 (August 2017) - Kim, H.-L.; Kwon, J.-S.; Choi, Y.-J.; Lee, U.-L.
Abstract: During a reduction malarplasty, precise sectioning of the zygomatic arch according to the plan formulated in the diagnostic stage is very important, because differences in the locations of the osteotomies in the left and right zygomatic arch will result in facial asymmetry, and arch osteotomies that are placed at locations other than those specified during planning elicit unwanted results. A method for the precise planning and sectioning of the zygomatic arch involving the use of computed tomography (CT) and a viewer program is presented herein. Furthermore, a case in which this method was applied during reduction malarplasty via a combined intraoral and external incision is described.